Primary elections and electoral outcomes: Evidence from the Spanish Socialist Party - Riccardo Ciacci; Ana Garcia-Hernandez; Jorge García-Hombrados; Laura Gismera; Antonio Nú\~nez-Partido (SERIEs - Journal of the Spanish Economic Association, 2022)
Using a regression discontinuity design and primary elections to select Spanish Socialist Party (PSOE) mayoral candidates as a case study, this paper investigates the causal link between primary elections and electoral outcomes. The results suggest that selecting the PSOE's mayoral candidate through primary elections has no effect on the percentage of votes and total votes received by the PSOE's candidate in local elections, the probability of gaining the mayorship and the local government's stability. On the other hand, the results suggest that PSOE's primary elections result in increased votes for competing political parties to the right of the PSOE and in reduced votes for competing parties to the left of the PSOE.
Keywords: D7; D72; 330